How to Finance Climate Change Policies? Evidence from Consumers' Beliefs - Francesco D'Acunto; Sascha Möhrle; Florian Neumeier; Andreas Peichl; Michael Weber; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2022)
Climate change policies have been rising to the top of the global political agenda, but how should governments finance them? Public economists propose solutions based on economic theory, but their political feasibility depends on voters' support, and ordinary households often neglect economic theory and have different views about efficiency and fairness. We design a large-scale information experiment to assess a representative population's beliefs about alternative forms of financing. We randomly provide information about which groups contribute more to or benefit from climate change and compare the support for alternative financing schemes across informed and uninformed consumers. Informed consumers strongly support the introduction of a VAT-style CO2 tax after learning that the rich contribute more to climate change than the poor, but do not support increasing taxes on older people when learning that they also pollute more. Moreover, consumers who learn that certain populations, due to luck, gain economically from climate change strongly oppose redistribution from gainers to losers of climate change. Consumers also oppose financing policies to fight climate change via public debt, implying higher costs for future generations. Market-based solutions, such as private insurance for those exposed to climate-change risk, are strongly opposed across the board.
Keywords: D64; D84; D91; F38; H23; Q54; 330; climate policy; fiscal policy; taxation; expectations; inequality